Mekanisme Corporate Governance dan Kecurangan Laporan Keuangan [Mechanisms of Corporate Governance and Financial Statement Fraud] - Fitri Ismiyanti; Chintia Prastichia (Universitas Pelita Harapan, 2015)
The purpose of this research is to examine factors that may affect fraud on financial statements that could encourage the emergence of corruption by management. This research uses banks as an industry sample because the banking industry is highly regulated and should report their financial statement to a central bank. Meanwhile, banks still frequently have fraudulent financial statements. Good corporate governance mechanisms indicated that banks have the capability to detect fraud in financial statements. This research focuses on testing factors that may affect the financial statements fraud which lead to the corruption of management. The data used in this research is financial statement data. Corporate governance mechanisms tested in this study are the number of commissioners, percentage of independent directors, number of commissioners meeting, percentage of largest share ownership, managerial ownership, long tenure of commissioners, and type of auditor. This research found that the number of commissioners and managerial ownership affects management's fraud, while the number of independent directors, the number of commissioners meeting, a long tenure managing director, large share ownership, and the type of auditor has no effect on fraud.